(untitled) (American Journal of IR 4.0 and Beyond, 2025)
The search for sustainability and operational efficiency in public supply chains has driven the adoption of resilient and innovative solutions, especially in the face of crises such as pandemics and logistical disruptions. This study aimed to identify, through a systematic literature review (RSL), the main strategies that integrate logistics efficiency, sustainability and resilience in the public sector and in local chains. The methodology was based on a qualitative analysis of 20 international articles selected between 2021 and 2025, with the support of Perplexity and thematic alignment criteria. The results were organized into four categories: (i) green digitalization and public logistics hubs; (ii) operational resilience strategies in the face of crises; (iii) sustainable innovation via AI, IoT, and circular economy; and (iv) public governance and collaborative partnerships. The literature shows that such strategies, when supported by public policies, adaptive infrastructure and efficient standardization, strengthen local chains and promote positive socio-environmental impacts. It is concluded that the integration between technological innovation, state capacity and intersectoral articulation is decisive to build resilient, sustainable and effective public chains.